The sphere of exposure: centering user experience in community science air monitoring - Westbrook, Marisa; Serrano-Salomón, Valentina; Pecenka, Jay; Sankhyan, Sumit; Hollo, Aniya K.; Miller, Shelly L.; Sullivan, Esther (Frontiers in Environmental Science, 2024)
Community science has increased in popularity in communities where residents hope to investigate the relationship between environmental issues and personal health. This study partnered with neighborhoods in the most polluted residential zip code in the US to conduct community science air quality monitoring. We conducted 60 semi-structured interviews after two monitoring deployments to understand participants' subjective experiences of pollution exposure, their engagement with low-cost air quality monitors, and their data interpretation. We utilize the environmental health concept 'exposure experience' to analyze how participants use personal monitors, understand their data, and reinterpret their pollution exposure as a result. We further explore how participants' understandings are circumscribed by the technological features of low-cost monitors. We find that participants adopt both protective and mitigating behavioral changes based on information gained from personal experiments and hypothesis testing while using the monitors. Of their own accord, 40% of participants in this study adopted mitigation behaviors after identifying sources that impacted their personal air quality. Our analysis reveals that real-time data accessibility through low-cost monitors builds exposure awareness and enables residents of environmental justice communities to test, validate, or invalidate sensory experiences and challenge existing assumptions. These findings point to specific pathways for using low-cost monitors to support individual decision-making and contribute to behavioral change. Findings also identify some limitations of low-cost sensors; designers of low-cost monitors should consider how composite Air Quality Scores may encourage community scientists to equally value scientifically-established pollutants (e.g. PM) with less scientifically established pollutants (e.g. TVOCs), without additional scientific training and health-related information.